The Effects of Sports Massage on EEG changes after submaximal exercise - Jang, E.K.; Yan, T.M.; Choi, K.S. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Previous research has indicated that sports massage therapy may play a positive role in the recovery of neurophysiological parameters following exercise. Therefore, the purpose of this study was to examine the effects of sports massage on electroencephalogram (EEG) patterns (alpha, delta and theta) following submaximal exercise. Methods Brain wave measures were used to determine the activity level of the cerebral cortex in the central nervous system. The subject group included 9 male college students with no particular clinical history or evidence of specific drug taking. Following a submaximal exercise treadmill test based on the Bruce protocol, subjects were allocated to undertake sports massage therapy or passive recovery. Brain wave recordings were made 4 times: prior to exercise, immediately after exercise, immediately after sports massage and 30 minutes after recovery. Brain wave changes were assessed using the Neuro-harmony computer measurement program based on measures taken at a neurophysiologic point. Data analysis utilized ANOVA and a paired t-test to determine the significance changes over time and between groups in the variables of interest. Results Study results indicated a significant change in alpha wave activity in the sports massage group after the treatment. Alpha wave activity is heightened when a degree of harmony occurs between body and soul and is associated with a level of relaxation and an overall state of calmness. Thus, the present findings may indicate that sports massage following exercise may create a relaxed state of the mind and body.